Anthropogenic Effects on Cloud Condensation Nuclei Distribution and Rain Initiation in East Asia. Issue 2 (23rd January 2020) - Liu, Chong; Wang, Tijian; Rosenfeld, Daniel; Zhu, Yannian; Yue, Zhiguo; Yu, Xing; Xie, Xiaodong; Li, Shu; Zhuang, Bingliang; Cheng, Tiantao; Niu, Shengjie
Key Points: The activated cloud condensation nuclei (CCN) into cloud droplets were nearly equally low (<300 cm −3 ) in inland areas with little anthropogenic emissions Anthropogenic emissions were responsible to the greatly elevated concentrations of CCN over and downwind of urban agglomeration The enhanced CCN increased cloud depth for rain initiation up to 4 km, further delayed and suppressed the precipitation over the most polluted regions Abstract: The recently developed method for retrieving cloud drop concentrations ( N d ), cloud base updraft, and supersaturation made it possible to map these properties over East Asia. It was done for the summers of 2013 to 2019, in conjunction to low level wind direction. The background CCN concentrations were nearly equally low (<300 cm −3 ) over minimally perturbed air masses to the south and east of the densely populated areas of China, over ocean, and to the north over northern China, Mongolia, and southern Siberia. This stood in large contrast to large concentrations of activated CCN into cloud droplets reaching up to 2, 000 cm −3 over and downwind of the densely populated regions over East Asia. Because cloud depth for rain initiation ( D c ) increased linearly with CCN concentrations, the enhanced CCN increased D c from a background of <1 km over ocean and 2 km to the north of China to D c > 4 km over the most polluted regions. Plain Language Summary: Cloud condensation nuclei (CCNs) are a subset of hygroscopic aerosol particles that nucleate water drops at supersaturations less than 1%, which is a research medium for studying aerosol‐cloud‐precipitation interaction. More CCN will lead the smaller the drops and the greater the liquid water content, the greater the cloud albedo, but their influence on cloud growth and on precipitation formation is still unclear. Because of the uncertainty in predicting the nucleation ability of atmospheric particles, the empirical method is usually used to measure the concentration of particles as CCN at various specified supersaturation in limited space and time. However, satellites can deliver the necessary global coverage for cloud observations with sufficient quality and long‐time frame, particularly in the ocean and inaccessible areas. This study first time uses a new method to acquire the distribution of CCN concentration of cloud base in East Asia. We use the satellite‐retrieved CCN concentrations to represent the actually activated CCN into cloud droplets. Our results show that the background CCN concentrations are nearly equally low (<300 cm −3 ) over northern China, Mongolia, and southern Siberia but high concentrations of activated CCN (>2, 000 cm −3 ) over and downwind of urban agglomeration. We also find that enhanced CCN can increase rain initiation height, then delay and suppress the precipitation over the polluted areas.